PENGARUH MEDIA PENYULUHAN TERHADAP PENGETAHUAN DAN SIKAP IBU TENTANG DIARE PADA ANAK DI PUSKESMAS BATU AJI KOTA BATAM - Amelia, Cevy; Rusdani, Rusdani (Universitas Batam, 2019)
According to Data from the Ministry of health, Indonesia diarrhea is still one of the major public health problems. This has caused high numbers of pain and still cause many deaths especially in infants and toddlers often and often give rise to extraordinary events. According to the report Data Service of Batam City Health States that the incidence of diarrhea in the year 2011 is a case and get 60,670 handling in the health service 30,556 cases. Diarrheal disease is a disease-based environment. There are two dominant factors i.e. water supply and disposal of feces. These two factors have an effect on the knowledge and attitude of the mother with the incidence of diarrhea in children. Knowledge of mother and mother's attitude is very influential in the occurrence of diarrheal disease. When the mother's knowledge of good, then the mother will know how to care for sick children diarrhea at home and the mother will also know about the signs to take medical treatment or refer to health facilities. Some health service conducted on community outreach in order to perform one to tackle the incidence rate of diarrhea and change the behavior of a society that still does not understand about the importance of a clean environment in order to be free from disease.This study is a quantitative study with a quasi-experimental design. This research was carried out In Clinics Batu Aji Batam city in July 2017. The population in this research is the mothers who seek treatment at Clinics Aji Stone. A total of 80 respondents were obtained, which were then processed and divided into 40 samples as the experimental group and 40 samples as the control group. Data were analyzed using a computer both univariatÂ and bivariat with T-Test Paired. The research results obtained in experimental group given socialization by the average rating are higher than in the control group whereas this study showed P-Value of 0,000 from the paired t-test on the knowledge and attitude of the experimental group. This showed that the socialization has a significant effect on knowledge and attitude.Socialization has a significant effect toward knowledge and Mother Attitude regarding Diarrhea at child at Batu Aji Health Centefrf of Batam City.